Privacy-aware knowledge discovery : novel applications and new techniques - Bonchi, Francesco; Ferrari, Elena (Chapman & Hall/CRC data mining and knowledge discovery series, 2011)
"Covering research at the frontier of this field, Privacy-Aware Knowledge Discovery presents state-of-the-art privacy-preserving data mining techniques for application domains, such as medicine and social networks, that face the increasing heterogeneity and complexity of new forms of data. Renowned authorities from prominent organizations not only cover well-established results; they also explore complex domains where privacy issues are generally clear and well defined, but the solutions are still preliminary and in continuous development. The book focuses on intricate, real-world applications in medicine, biology, the web, social networks, and mobility observation systems.